The idea of gaiety in Yeats's lyric poetry - Brady, Bronwyn (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1990)
In June 1917 W.B. Yeats wrote to his father : Much of your thought resembles mine . . but mine is part of a religious system more or less logically worked out, a system which will I hope interest you as a form of poetry. I find the setting it all in order has helped my verse, has given me a new framework and new patterns. (Wade 1954, 627) The new framework and new patterns that he claimed to have found in his system generated a new, and for Yeats, radically different sort of poetry. Before 1919 (The Wild Swans at Coole), the poetry had as its subject various traditional themes: the pity of love; the romance and heroism of Irish mythology; the threat of age, change and death. The poetry up to this point is, formally speaking, highly skillful, but locked into its own admissions of failure to touch or incorporate reality in any but a romantically defeatist way. However, the order which Yeats refers to in his letter, and the system he generated as a propaedeutic to this new order, once assimilated into the habit and texture of the poetry, generated new topics of its own which made those of the earlier work seem subjective, self- indulgent and intellectually uninformed. Yeats's poetry now changed drastically in focus and form, from subjective to objective poetry. Whereas the earlier poetry had opposed reality with romantic heroism or selfdestructive despondency, the poetry subsequent to his change of practice, incorporates a new vision of reality as the intrinsic architechtonics of poetry itself. Now the measure of human and aesthetic completion is no longer an inexplicable and inscrutable sadness, but an intelligent and informed detachment, an energy of mind that Yeats called "gaiety". My thesis explores this energy of mind and what it meant for Yeats and his poetry. My contention is that the idea of gaiety provides a way for Yeats to grant meaning to his life, a way for him to create himself. As the poetry is completed thanks to the new system, so is the poet. In order to see this, it is necessary to read the poems as a series of collections, or stories, that resonate back and forth with meaning and qualification and understanding. Yeats's system is his myth, and he writes his poetry in terms of and informed by that myth, shaping and re-shaping the experience of the created and fictional self until it has meaning in a way that the real self does not. The thesis explores this process of creation firstly in theoretical terms, using Lotman's ideas of Story and Myth, and looking at Yeats's intellectual and poetic inheritance. It goes on to examine some of the great poems in an attempt to define gaiety, and how Yeats achieves it in the poetry, and then to look at the early, pre-system poems to see how they differ. Finally, it takes the last of Yeats's lyric collections, Last Poems, and shows how gaiety works in the most mature poetry when the poems are read as narrative events within a story.
Keywords: Yeats, W. B. (William Butler), 1865-1939 -- Criticism and interpretation; Lyric poetry -- History and criticism